Iraq Economic Monitor, Spring 2022 : Harnessing the Oil Windfall for Sustainable Growth - World Bank (Washington, DC: World Bank, 2022)
With a Special Focus COVID-19 and the Human Capital Crisis: Recovering Educational Losses for Future Productivity and Growth